Answer:f=−
7
x
2
+1−2g−x
Explanation:
1 Subtract {x}^{2}x
2
from both sides.
2{x}^{2}+1-g-x-{x}^{2}=-7f+g2x
2
+1−g−x−x
2
=−7f+g
2 Simplify 2{x}^{2}+1-g-x-{x}^{2}2x
2
+1−g−x−x
2
to {x}^{2}+1-g-xx
2
+1−g−x.
{x}^{2}+1-g-x=-7f+gx
2
+1−g−x=−7f+g
3 Subtract gg from both sides.
{x}^{2}+1-g-x-g=-7fx
2
+1−g−x−g=−7f
4 Simplify {x}^{2}+1-g-x-gx
2
+1−g−x−g to {x}^{2}+1-2g-xx
2
+1−2g−x.
{x}^{2}+1-2g-x=-7fx
2
+1−2g−x=−7f
5 Divide both sides by -7−7.
-\frac{{x}^{2}+1-2g-x}{7}=f−
7
x
2
+1−2g−x
=f
6 Switch sides.
f=-\frac{{x}^{2}+1-2g-x}{7}f=−
7
x
2
+1−2g−x